PERANCANGAN INVERTER SATU FASA OFF-GRID MENGGUNAKAN DSPIC30F4011 DENGAN KONTROL ARUS METODE PROPORTIONAL RESONANT - Suroso, Segal Mancini; Setiawan, Iwan; Winardi, Bambang (Universitas Diponegoro, 2018)
The availability of fossil as fuel in conventional power plants is running low. This causes the use of renewable energy such as photovoltaic (PV) technology becomes very important. PV systems required inverters for converting DC voltage into AC voltage, where the quality of the inverter output current is very influential on the quality of power. Therefore, it is necessary to control the inverter current output which serves to improve the system response and minimize the current harmonics. In this research, a H-Bridge type of one phase Inverter is designed using 16-bit DSPIC30F4011 microcontroller with current control proportional resonant method. The inverter output current is fedback by the ACS712-05B current sensor. The test is carried out with the reference current range of 1 - 3 A on the load variation 7 Î© and 12 Î©. The test results show the actual current waveform of the inverter output is able to follow the reference current changes. Inductor value that not suitable and the effect of switching cause the ripple is still happening. The higher the output voltage of the inverter will result in the total current harmonic distortion becoming smaller.